2013
DOI: 10.1039/c3cc44374d
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous metal formates for krypton/xenon separation

Abstract: Metal(II) formates (Co and Ni) show a significantly larger heat of adsorption for xenon than krypton across all loadings due to size selectivity in the primary adsorption site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 13 publications
(18 reference statements)
2
42
0
Order By: Relevance
“…[18] While the overall uptake remains limited due to the rather small pore volume, the fact that the isosteric heat of H 2 adsorption is almost independent of the loading could be interesting for hydrogen storage applications. In the field of gas separation, recent efforts have addressed the separation of Xe/Kr mixtures using Co(fa) 2 and Ni(fa) 2 , [19] and the selective adsorption of methane over N 2 in the same two systems. [20,21] Relatively high M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 selectivities were observed for these challenging separations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] While the overall uptake remains limited due to the rather small pore volume, the fact that the isosteric heat of H 2 adsorption is almost independent of the loading could be interesting for hydrogen storage applications. In the field of gas separation, recent efforts have addressed the separation of Xe/Kr mixtures using Co(fa) 2 and Ni(fa) 2 , [19] and the selective adsorption of methane over N 2 in the same two systems. [20,21] Relatively high M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 selectivities were observed for these challenging separations.…”
Section: Introductionmentioning
confidence: 99%
“…[26,27] Monte Carlo simulations of adsorption were also employed to aid the aforementenioned experimental investigation of Xe/Kr separation. [19] Electronic structure methods, such as density-functional theory (DFT), can be employed to study the interaction of porous materials with adsorbed guest molecules from first principles. An important aspect is the inclusion of dispersion interactions, which are omnipresent in adsorption phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs have several advantages as compared to zeolites: cheaper and simpler synthesis, high diversity of pore structures, and numerous possibilities for postsynthetic modifications. Despite the importance of MOFs for noble gas storage and separation, only a few studies of krypton and xenon adsorption are reported to date [1][2][3][4][5][6][7][8][9][10][11][12] and only three studies of adsorption sites of noble gases in MOFs by means of X-ray or neutron diffraction, [13][14][15] despite the fact that the major adsorption sites and their binding energies are the key features of a material that determines its adsorption properties at a given temperature and pressure, and their identification is a basis for further modifications of the crystal structure of the MOF in order to achieve maximal storage capacity and selectivity. The study of noble gas adsorption in HKUST-1 15 revealed that the interaction of noble gases with MOFs can be completely different from the adsorption of other atoms and molecules like D 2 , C 2 H 2 , CO 2 , or CH 4 (methane is a nonpolar gas whose diameter and polarizability are similar to those of Kr).…”
Section: Introductionmentioning
confidence: 99%
“…45,46 Xenon and krypton are also products of the nuclear fission of uranium and plutonium; 40 porous materials could be used to capture the radioactive xenon and krypton in the processing of used nuclear fuel. [47][48][49] Experiments regarding xenon and krypton adsorption 44,48,[50][51][52][53][54][55][56][57][58][59][60][61][62] suggest that it may be feasible to use nanoporous materials in an adsorption-based process to separate a Xe/Kr mixture.…”
mentioning
confidence: 99%